Catastrophic Events and Mass Extinctions: Impacts and Beyond 2002
DOI: 10.1130/0-8137-2356-6.505
|View full text |Cite
|
Sign up to set email alerts
|

Continental Triassic-Jurassic boundary in central Pangea: Recent progress and discussion of an Ir anomaly

Abstract: The Triassic-Jurassic (Tr-J) boundary marks one of the five largest mass extinctions in the past 0.5 b.y. In many of the exposed rift basins of the Atlantic passive margin of eastern North America and Morocco, the boundary is identified as an interval of stratigraphically abrupt floral and faunal change within cyclical lacustrine sequences. A comparatively thin interval of Jurassic strata separates the boundary from extensive overlying basalt flows, the best dates of which (ca. 202 Ma) are practically indistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 60 publications
3
52
0
Order By: Relevance
“…There are no reports of iridium enrichment of similar magnitude at any of the marine TJB sections . Olsen et al (2002b) discounted a volcanic source for the anomaly on the basis of a lack of correlation of iridium concentration with other trace elements in the Newark basin section. However, a similar lack of correlation is observed between iridium and other siderophile elements, such as cobalt, nickel, or chromium, which are potential indicators of an extraterrestrial origin (Koeberl, 1998;Kyte, 2002;Olsen et al, 2002b).…”
Section: Osmium and Strontium Isotopesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no reports of iridium enrichment of similar magnitude at any of the marine TJB sections . Olsen et al (2002b) discounted a volcanic source for the anomaly on the basis of a lack of correlation of iridium concentration with other trace elements in the Newark basin section. However, a similar lack of correlation is observed between iridium and other siderophile elements, such as cobalt, nickel, or chromium, which are potential indicators of an extraterrestrial origin (Koeberl, 1998;Kyte, 2002;Olsen et al, 2002b).…”
Section: Osmium and Strontium Isotopesmentioning
confidence: 99%
“…Furthermore, the "first common appearance" of Convolutispora klukiforma was also cited as evidence of the Jurassic age of the C. meyeriana palynofloral zone. In the Jacksonwald syncline of the Newark basin, Olsen et al (2002b) place this boundary within 10 m to 15 m of the base of the Orange Mountain Basalt. In the Fundy basin, at Partridge Island, this transition is placed just 20 cm to 30 cm below the base of the North Mountain Basalt (Fowell and Traverse, 1995;Olsen et al, 2005).…”
Section: Palynostratigraphic Constraintsmentioning
confidence: 99%
“…The causes of this ecosystem collapse are still under discussion. Climatic changes, sealevel changes, oceanic anoxia (Hallam 1997;Hallam & Wignall 1997b), as well as flood basalt volcanism (Marzoli et al 1999;Hesselbo et al 2002;Pálfy 2003) and extraterrestrial impacts (Olsen et al 2002) are frequently cited agents that could be responsible for this sudden decrease of biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…Three main possible drivers are considered: The first is the emplacement of a large igneous province (the Central Atlantic Magmatic Province, CAMP) that was associated with the initial break up of Pangaea (Wilson 1997), the second is the possible impact of a large meteorite (Olsen et al 2002) (Nomade et al 2007;Verati et al 2007) confirmed the isochroneity of CAMP volcanism and major changes in marine and terrestrial ecosystems at the Triassic/Jurassic boundary. The palynological data of the present study support this hypothesis.…”
mentioning
confidence: 99%
“…Olsen et al 2002;Voigt et al 2006;Hornung et al 2007); in the NW Tethyan realm, the Mecsek Mountains of South Hungary is the only area where continuous sections of coalbearing facies are present. Pécs and Komló were the two regional centers of coal mining ( Fig.…”
Section: Introductionmentioning
confidence: 99%